An Experimental Investigation on Effect of GFRP Sheets on Deep Beams - Ameeruddin Arafat, Mohammed; Sunil Pratap Reddy, S; Riyaz, Syed (International Journal of Computer Sciences and Engineering, 2025)
Reinforced concrete deep beams are widely used as transfer girders in offshore structures and foundations, walls of bunkers and load bearing walls in buildings. The presence of web openings in such beams is frequently required to provide accessibility such as doors and windows or to accommodate essential services such as ventilating and air conditioning ducts. Enlargement of such openings due to architectural/mechanical requirements and/or a change in the building’s function would reduce the element’s shear capacity, thus rendering a severe safety hazard. Limited studies have been reported in the literature on the behavior and strength of RC deep beams with openings. When such enlargement is unavoidable adequate measures should be taken to strengthen the beam and counteract the strength reduction.The present experimental investigation deals with the study of deep beams containing openings and the validation of results with FEM model using ANSYS. A total of 5 deep beams with openings are casted without shear reinforcements and are tested under three-point loading. Test specimen has a cross section of 150x460 mm and a total length of 1200 mm. Two circular openings, one in each shear span, are placed symmetrically about the mid-point of the beam. The structural response of RC deep beams with openings was primarily dependent on the degree of the interruption of the natural load path. Externally bonded GFRP shear strengthening around the openings was found very effective in upgrading the shear strength of RC deep beams. The strength gain caused by the GFRP sheets was in the range of 68–125%. Finite element modeling of RC deep beams containing openings strengthened with GFRP sheets is studied using ANSYS and the results are compared with experimental findings.